Kajian Literatur: Keterampilan Kolaborasi Peserta Didik Dalam Pembelajaran IPA - Nurfitra Yanto; Adila; Muhammad Farid; Yahya (Kappa Journal, 2024)
Collaboration skills are one of the skills that are needed in 21st Century learning. The research method used is a literature study that examines collaboration skills in science learning. A total of 15 articles that examine collaboration skills are collected and then analyzed so as to get recommendations regarding literature studies. The results of the study can be concluded that applying several learning models such as problem-based learning (PBL), Project-Based Learning (PjBL) can increase productivity, efficiency, and quality of teamwork results. In addition to learning models, the right teaching materials can affect the ability of collaboration skills in science learning. The types of teaching materials that should be used are STEM and discovery-based teaching materials.